ANALISIS YURIDIS TINDAKAN PERUSAHAAN PEMBIAYAAN TERHADAP DEBITUR YANG LALAI MEMBAYAR KEWAJIBAN KREDIT KENDARAAN BERMOTOR RODA DUA DIKOTA PONTIANAK - RESTUA BERESDO SINAGA NIM. A1011151202 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract FIF GROUP Pontianak Branch is one of the finance companies that provides consumer financing facilities in the form of special loan funds only for the purchase of two-wheeled Honda branded vehicles on credit. In the financing process, FIF GROUP Pontianak Branch believes that consumers will be able to pay off all of their debts. But in fact, consumers (debtors) who buy two-wheeled motorized vehicles on credit do not all fulfill their obligations in paying installments or are negligent in paying their credit obligations for their two-wheeled motorized vehicles. Therefore, the FIF GROUP Pontianak Branch took action against debtors who were negligent in paying their loan obligations for two-wheeled motorized vehicles.As for the problem in this study is